Analysis of the interaction between properties and microstructure of construction ceramics - Khomenko, Olena; Sribniak, Nataliia; Dushyn, Vladyslav; Shushkevych, Viacheslav (Eastern-European Journal of Enterprise Technologies, 2018)
We have defined the basic properties of ceramic bricks for various purposes. The microstructure and phase composition of ordinary, facing and clinker bricks were investigated. We have established the interrelation between the microstructure and phase composition of the examined materials and water absorption, mechanical strength at compression, and frost resistance. The research results allowed us to identify patterns in the formation of a ceramic sherd and explain the physical-chemical processes during sintering. It was established that ordinary brick mostly contains the thermally altered clay substance with a low amount of the glass-phase. Given the above, due to the incomplete liquid-phase sintering, the ordinary brick has high water absorption values (10‒14 %) at low strength (7.5‒12.5 MPa). Facing brick has the more developed glass-phase, which firmly binds the crystalline phase. The latter is represented by such minerals as β-quartz, microcline, albite, mullite, etc. The main task in the facing brick production is to ensure the optimal dispersion of starting raw materials and to achieve even distribution of minerals throughout the entire volume of the product. Clinker brick has a more complex mechanism of sintering because when using the starting particulate mass, it is required to obtain a dense homogeneous structure of products. The main features of the ceramic mass are the introduction to its composition of emaciated additives that would ensure the resistance of products against deformation during annealing, and marshes, which should ensure the intensive liquid-phase sintering at annealing. When annealing such articles, it is necessary to select the proper temperature-time mode, which would match the sintering interval of the basic clay material. This is required to ensure that, on the one hand, a strong dense structure of the product is obtained, with a water absorption of 4‒5 %, and, on the other hand, that such kinds of defects as deformation, cracking, «over-annealing», swelling, etc. are avoided. Research results could be applied under industrial conditions at enterprises in order to control product quality and eliminate possible causes of defects related to violation of the technological production mode.